2008
DOI: 10.1208/s12249-008-9136-7
|View full text |Cite
|
Sign up to set email alerts
|

Preformulation Studies of a Prodrug of Δ9-Tetrahydrocannabinol

Abstract: Abstract. Preformulation studies were performed on a hemiglutarate ester prodrug of Δ 9 -tetrahydrocannabinol (THC-HG), to facilitate the development of stable formulations by hot-melt methods. The various studies performed included solid-state thermal characterization, pKa, logP, aqueous and pH dependent solubility, pH stability and effect of moisture, temperature and oxygen on solid-state stability. A hot-melt method was utilized to fabricate THC-HG incorporated poly (ethylene oxide) (PEO) matrices and the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…Moreover, these results were View Article Online compared favorably with the values obtained for spectrophotometry 28 and HPLC. 29 In the case of sample 1, the average value obtained by amperometry showed to be the same of that found by spectrophotometry and it was very close to the result obtained by HPLC. A significance test (null hypothesis) was applied to results showed in Table 1, resulting in experimental t-values of 1.00 (for amperometry and spectrophotometry) and 0.33 (for amperometry and HPLC).…”
Section: Determination Of Promethazine Hydrochloridesupporting
confidence: 81%
See 3 more Smart Citations
“…Moreover, these results were View Article Online compared favorably with the values obtained for spectrophotometry 28 and HPLC. 29 In the case of sample 1, the average value obtained by amperometry showed to be the same of that found by spectrophotometry and it was very close to the result obtained by HPLC. A significance test (null hypothesis) was applied to results showed in Table 1, resulting in experimental t-values of 1.00 (for amperometry and spectrophotometry) and 0.33 (for amperometry and HPLC).…”
Section: Determination Of Promethazine Hydrochloridesupporting
confidence: 81%
“…High performance liquid chromatography analyses of the commercial samples were performed following a methodology described in the literature. 29 About 15 mg of macerated tablets were weighed and dissolved in 10.0 mL of methanol. The samples were centrifuged at 5000 rpm over 15 minutes.…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Different polymers and drugs have been employed and reported in the literature for obtaining drug loaded hotmelt extruded films for various indications and are summarised in Repka and co-workers have conducted extensive research on the use of HME for the manufacture of mucoadhesive buccal films. They successfully evaluated different matrix formers and additives for the processing of the blend prior to extrusion [61,62,63,64]. In an early investigation, it was found that even though films containing exclusively HPC could not be obtained, the addition of plasticizers, such as triethyl citrate, PEG 2000/8000, or acetyltributyl citrate, allowed for the manufacture of thin, flexible, and stable HPC films [65].…”
Section: Films By Hot-melt Extrusionmentioning
confidence: 99%